A report on the symposium “Juri Lotman and sociosemiotics” (Elva, Estonia, 19–20 May 2017) - Gramigna, Remo (Sign Systems Studies, 2018)
A report on the symposium “Juri Lotman and sociosemiotics” (Elva, Estonia, 19–20 May 2017).